FUNCTIONAL ASSESSMENT OF MASTICATORY MUSCLES IN ADAPTATION TO COMPLETE REMOVABLE PROSTHESES - S. A. Shemetov; I. M. Martynenko; R.V. Petrenko; N.A. Ryabushko (Український стоматологічний альманах)
In terms of scientific research, especially in the enhancement and application of new technologies of subjective quality assessment methods of prosthetics is not enough, therefore, the most objective and informative electromyography recognized the essence of which consists in registration of biopotentials of the masticatory muscles.